Employees’ Post Lockdown Perspectives on Communication in Telework - Butoi, Elisabeta; Ștefănuț, Dinuța-Maria (Acta Universitatis Danubius. Œconomica, 2022)
The Covid-19 outbreak forced organisations to shift from face-to-face work to telecommuting in a very short time. The employers and employees had to quickly to perform tasks at least like before lockdown. Therefore, the focus of this study was to examine the main determinants of employees’ perceived communication and telework satisfaction. The data was gathered from employees of different companies. The quantitative approach was implemented to analyse the subject. The findings show a constructive influence of the support offered by employers to employees who have to adopt digital communication. The adaptation of mediated communication impacts the teleworkers’ tasks performance in terms of collaborative activities implicating colleagues and supervisors. The teleworkers’ job performance is positively affecting employees’ perception of satisfactory digital communication. The family conflicts during telecommuting are not difficult to manage, thus telework is appropriate and digital communication favourable. The teleworkers work-life balance is predicted by the perceived satisfaction with the mediated communication experience through the communication channels used. The findings also emphasize the respondents’ preference for future teleworking. This study findings serve further research and employers’ approach of communication with and between teleworkers.